1997
DOI: 10.1074/jbc.272.46.29181
|View full text |Cite
|
Sign up to set email alerts
|

NAG-2, a Novel Transmembrane-4 Superfamily (TM4SF) Protein That Complexes with Integrins and Other TM4SF Proteins

Abstract: Transmembrane-4 superfamily (TM4SF) proteins form complexes with integrins and other cell-surface proteins. To further characterize the major proteins present in a typical TM4SF protein complex, we raised monoclonal antibodies against proteins co-immunoprecipitated with CD81 from MDA-MB-435 breast cancer cells. Only two types of cell-surface proteins were recognized by our 35 selected antibodies. These included an integrin (alpha6beta1) and three different TM4SF proteins (CD9, CD63, and NAG-2). The protein NAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 52 publications
1
59
1
Order By: Relevance
“…The present study, for the first time, screened multiple SCLC cell lines for tetraspanin expressions. All tetraspanins tested in this study (CD9, CD63, CD81, CD82, CD151, and NAG-2) are present in multiple organs including the lung (Nagira et al, 1994;Fitter et al, 1995;Oritani et al, 1996;Tachibana et al, 1997;Lantuejoul et al, 1998). The flow cytometry data indicated that, among these molecules, expressions of CD9 and NAG-2 were less frequent in SCLC compared with NSCLC.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The present study, for the first time, screened multiple SCLC cell lines for tetraspanin expressions. All tetraspanins tested in this study (CD9, CD63, CD81, CD82, CD151, and NAG-2) are present in multiple organs including the lung (Nagira et al, 1994;Fitter et al, 1995;Oritani et al, 1996;Tachibana et al, 1997;Lantuejoul et al, 1998). The flow cytometry data indicated that, among these molecules, expressions of CD9 and NAG-2 were less frequent in SCLC compared with NSCLC.…”
Section: Discussionmentioning
confidence: 86%
“…M38 and M104, mouse MoAbs against CD81 and CD82, respectively, were gifts from Dr O Yoshie (Kinki University School of Medicine, Osaka, Japan). 6H1, 5C11, and NAG-1, mouse MoAbs against CD63, CD151, and NAG-2, respectively, and A1A5 and SG/19, mouse anti-b1 integrin MoAbs, were previously described (Tachibana et al, 1996;Berditchevski et al, 1997;Tachibana et al, 1997;Yauch et al, 1998). A mouse anti-N-CAM MoAb, ITK-2, was established in our laboratory and characterized previously (Saito et al, 1991).…”
Section: Antibodiesmentioning
confidence: 99%
“…CD53 is restricted to leukocytes [55] and is absent from platelets [56, 57], so its expression does not appear to overlap with Tspan9. Tspan4 appears to be more widely expressed [58] but not by platelets [56, 57]. These expression profiles could explain how a platelet phenotype has been identified in the Tspan9-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this family tend to associate both with each other, and with cell-type-specific partner proteins. For example, CD81 associates in B cells with CD19 (25) whereas in T cells it associates with CD4 and CD8 (26)(27)(28). Tetraspanins and their partners assemble in the membrane in tetraspaninenriched microdomains (TEMs), which facilitate key cellular functions.…”
Section: A Ctivation Of Naïve T Cells Requires Two Independent Signalsmentioning
confidence: 99%